Perceraian dalam Kristen - Midtra Yhera, Midtra Yhera; Nuria Peronica, Octa; Mikhel Nicolaus, Reonald; Sarmauli, Sarmauli (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research discusses the issue of marriage and divorce from a Christian perspective, with a focus on Biblical teachings and their impact on the family. Marriage is seen as a sacred bond that reflects Christ's relationship with the congregation, while divorce is a topic that causes differences of opinion among churches. Some churches reject divorce in all forms, while others allow it in certain cases. Divorce in a Christian family can have a significant impact, especially on children who experience emotional and behavioral difficulties. This research aims to identify the meaning of divorce in the Christian faith, its causes and impacts, as well as encouraging efforts to build strong families based on God's love. This research examines Christian views on divorce through a literature review, with a focus on the theological, social, and emotional impacts of divorce. The research results show that divorce is seen as a violation of the marriage bond which should last a lifetime. Although the church generally opposes divorce, some cases such as infidelity or abandonment of a spouse by an unbeliever may be acceptable reasons. Divorce has far-reaching impacts, especially for children who experience emotional and social difficulties. This research emphasizes the importance of commitment, forgiveness, and guidance in maintaining the integrity of a marriage and avoiding the negative impacts of divorce.